2010
DOI: 10.1037/a0019913
|View full text |Cite
|
Sign up to set email alerts
|

The Aberrant Salience Inventory: A new measure of psychosis proneness.

Abstract: Aberrant salience is the unusual or incorrect assignment of salience, significance, or importance to otherwise innocuous stimuli and has been hypothesized to be important for psychosis and psychotic disorders such as schizophrenia. Despite the importance of this concept in psychosis research, no questionnaire measures are available to assess aberrant salience. The current research describes 4 studies designed to develop and validate the Aberrant Salience Inventory (ASI) as a measure of aberrant salience. In St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
206
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(223 citation statements)
references
References 102 publications
(131 reference statements)
14
206
1
2
Order By: Relevance
“…After EFA and CFA, convergent validity was the preferred technique used in the vast majority of the studies included in this review (e.g., Brun et al 2014;Cicero et al 2010). This finding is consistent with prior research (Bastos et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After EFA and CFA, convergent validity was the preferred technique used in the vast majority of the studies included in this review (e.g., Brun et al 2014;Cicero et al 2010). This finding is consistent with prior research (Bastos et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cicero et al (2010) reported that the main limitation of their study was the fact that none of the items were reverse-scored. Although some methodologists claim that reverse scoring is necessary to avoid acquiescence among participants, this advice should be taken with caution.…”
Section: Item Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overevaluation of familiarity indicated that patients might experience meaningless sounds as more significant than healthy subjects in agreement with schizophrenic individuals' perceptual reports by using the ASI scale (Cicero et al, 2010) and with the aberrant salience hypothesis developed by Kapur. This result might be accurately compared with previous ones from Nielzen, Olsson, and Ohman (1993), who demonstrated that patients judged complex nonverbal nonenvironmental sounds as more attractive than healthy subjects.…”
Section: Abnormal Perceptual Experience Of Abstract Soundsmentioning
confidence: 80%
“…To interpret the behavioral and electrophysiological results of this study, two main perspectives afford us a theoretical framework, which are inspired from the perceptual scales previously cited: the hypothesis of "sensory gating deficit" (related to SIAPA; Bunney et al, 1999) and the "aberrant salience" hypothesis (related to ASI; Cicero et al, 2010). These two fi-ameworks will be considered as complementary.…”
mentioning
confidence: 99%